2012
DOI: 10.1111/j.1532-5415.2011.03742.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual Function in the ‘Oldest‐Old’ 1 Year After Comprehensive Vision Rehabilitation

Abstract: for GNB isolation were polypharmacy (P = .03) and history of IHD (P = .01). CONCLUSIONMore than one-third of the LTC residents sampled had GNB isolated from their oropharynx. This rate was three times as high as in community-dwelling older persons of similar age and sex. These findings are in keeping with those previously published. 7,8 Although LTC residents had a higher incidence of LRTI in the year before sampling and received more antibiotics, no association was found between these factors and the isolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In Stelmack et al, 16 study devices were provided to subjects at no cost. In the Jackson et al, 17 study rehabilitation did not include free provision of devices for all subjects. Devices were provided by local or state agencies for some patients or could be purchased by patients if they chose.…”
Section: Discussionmentioning
confidence: 99%
“…In Stelmack et al, 16 study devices were provided to subjects at no cost. In the Jackson et al, 17 study rehabilitation did not include free provision of devices for all subjects. Devices were provided by local or state agencies for some patients or could be purchased by patients if they chose.…”
Section: Discussionmentioning
confidence: 99%
“…Low-vision rehabilitation services, which mainly focus on various optical and non-optical devices and techniques to enhance residual vision or substitute for lost vision, is important in helping people regain their independence, take care of personal needs, and participate in work/leisure activities [104]. Studies have suggested that appropriate rehabilitation can significantly improve HRQOL for visually impaired patients including those with glaucoma [83] [105] and the oldest old [106]. However, it has been suggested that the present system of low-vision care is less than optimal in many countries, and that only 10% -15% of visually impaired people can access low-vision services [107].…”
Section: Factors Influencing Hrqolmentioning
confidence: 99%
“…Effect sizes were calculated using z values 24. Furthermore, since data did not meet the assumptions for a nonparametric correlational test, a Kruskal-Wallis test analyzed differences between GDS-SF scores and 3 older adult age groups within the sample: “old” (between 65 and 74 years of age), old old” (between 75 and 84 years of age), and “oldest old” (85 years and older) 25…”
Section: Methodsmentioning
confidence: 99%
“…24 Furthermore, since data did not meet the assumptions for a nonparametric correlational test, a Kruskal-Wallis test analyzed differences between GDS-SF scores and 3 older adult age groups within the sample: "old" (between 65 and 74 years of age), old old" (between 75 and 84 years of age), and "oldest old" (85 years and older). 25 A Kruskal-Wallis test assessed differences between the number/types of diagnoses and GDS-SF scores and between functional impairment and GDS-SF scores. GDS-SF scores were used as a continuous variable for data analysis.…”
Section: Statistical Analysesmentioning
confidence: 99%